the implementasi pendidikan seksualitas anak melalui pembelajaran fikih - jauhari faruq, dukan (Pendidikan Islam Pascasarjana IAIN Jember, 2019)
the implementation of sexuality education in schools provides an important role for children's development. with sexuality education through fiqh learning the teacher can provide habituation and instill the value of responsibility to the child by introducing the tasks and functions of the body based on the sex of the child. this study aims to find out (1) how the implementation of child sexuality education through fiqh learning in the thaharah chapter ?, (2) how is the implementation of child sexuality education through the jurisprudence chapter? this study used a qualitative descriptive approach with multi-site study, because it was conducted in two educational institutions namely mima 34 hasyim asy'ari ambulu jember and mi 45 as-sunniyyah kencong jember. techniques for collecting data through interviews (with principals, fiqh maple teachers, homerooms, and students), observations, and study documentation developed through research institutions. the results of the study are as follows (1) the implementation of child sexuality education through fiqh learning in the thaharah chapter is through: (a) menstrual material, circumcision, and baligh boundaries; (b) the method used is lecture, question and answer and story telling; (c) the selected media is a blackboard; (d) the obstacles encountered in this learning are the selection of the right language and class conditions which are still mixed between men and women. the solution taken is to use scientific language or arabic and separate the male and female bench series. (2) implementation of child sexuality education through jurisprudence learning chapter prayer is through: (a) material about genitals and differences between men and women in prayer; (b) the method used is lecture, question and answer, and demonstration; (c) the selected media are three-dimensional visual instruments in the form of artificial objects such as barbie dolls and original objects in the form of the students themselves; (d) barriers encountered in this learning are the condition of students who are still very early in age, a mindset that is still limited / concrete, and knowledge that is still small. so the solution chosen is to explain in a simple language and provide an easy picture by using concrete media such as barbie dolls or from the students themselves.